The private sector and the labour insertion problem of the most vulnerable segments - Sconfienza, María Eugenia (Revista Española de Desarrollo y Cooperación, 2023)
In periods in which sustainable development interventions spread throughout society, it is possible to ask oneself about the place of labour inclusion issues in the most vulnerable sectors. In a segmented labor market as the argentine one wonders what are the CSR strategies linked to this problem.